2001
DOI: 10.1074/jbc.m007484200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Levosimendan, a Calcium Sensitizer, to Cardiac Troponin C

Abstract: Levosimendan is an inodilatory drug that mediates its cardiac effect by the calcium sensitization of contractile proteins. The target protein of levosimendan is cardiac troponin C (cTnC). In the current work, we have studied the interaction of levosimendan with Ca 2؉ -saturated cTnC by heteronuclear NMR and small angle x-ray scattering. A specific interaction between levosimendan and the Ca 2؉ -loaded regulatory domain of recombinant cTnC C35S was observed. The changes in the NMR spectra of the N-domain of ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 33 publications
2
111
0
5
Order By: Relevance
“…Levosimendan treatment enhances cardiac efficiency without an increase in oxygen demand associated with enhanced contractility induced by other agents, such as dobutamine, currently in clinical use (see review by Endoh [47]). Levosimendan increases myofilament Ca 2+ sensitivity by a molecular mechanism that appears to involve direct binding to the N-domain of Ca 2+ -saturated cTnC [49,63], although this was challenged by a study showing that levosimendan did not bind to cTnC or a cTnC/cTnI complex [64]. A later report has shown that the inability to observe levosimendan binding to cTnC was in part due to sample degradation and the use of a recombinant cTnC having C35 and C84 mutated to serines [63].…”
Section: Levosimendan and Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Levosimendan treatment enhances cardiac efficiency without an increase in oxygen demand associated with enhanced contractility induced by other agents, such as dobutamine, currently in clinical use (see review by Endoh [47]). Levosimendan increases myofilament Ca 2+ sensitivity by a molecular mechanism that appears to involve direct binding to the N-domain of Ca 2+ -saturated cTnC [49,63], although this was challenged by a study showing that levosimendan did not bind to cTnC or a cTnC/cTnI complex [64]. A later report has shown that the inability to observe levosimendan binding to cTnC was in part due to sample degradation and the use of a recombinant cTnC having C35 and C84 mutated to serines [63].…”
Section: Levosimendan and Analogsmentioning
confidence: 99%
“…Levosimendan increases myofilament Ca 2+ sensitivity by a molecular mechanism that appears to involve direct binding to the N-domain of Ca 2+ -saturated cTnC [49,63], although this was challenged by a study showing that levosimendan did not bind to cTnC or a cTnC/cTnI complex [64]. A later report has shown that the inability to observe levosimendan binding to cTnC was in part due to sample degradation and the use of a recombinant cTnC having C35 and C84 mutated to serines [63]. It appears that C84 is necessary for the interaction of levosimendan and cTnC.…”
Section: Levosimendan and Analogsmentioning
confidence: 99%
“…Levosimendan can bind directly to troponin C 42,43 , but subsequent studies showed that the binding of levosimendan and its active metabolite, OR-1896, to troponin C is very weak 44 , with a K d of ~1 mM 45,46 . It was postulated that the reactive malononitrile moiety of levosimendan may form a covalent bond to Cys84 of cardiac troponin C 47 , although this reactive group is not present in OR-1896. Thus, the physiological significance of the weak levosimendan-troponin C interaction is unclear 48,49 .…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%
“…Positive inotropic drugs are added to the conventional treatment when peripheral hypoperfusion signs are present. Levosimendan does not distinctively potentiate intracellular cyclic adenosine monophosphate and calcium levels; in contrast to other inotropic drugs, levosimendan stabilizes cross-bonds between actin and myosin, leading to enhanced contractility (8)(9)(10). Levosimendan stimulates adenosine triphosphate-sensitive potassium channels on vascular smooth muscles, resulting in arterial and venous vasodilatation.…”
Section: Discussionmentioning
confidence: 99%